ICT-Enabled Smart Environment Development: A Systematic Review of Technologies, Functional Roles, and Environmental Outcomes - Mashudah Sabilaturrizqi; Dhea Rahma Dianti; Sindy Nindia Maretha HarisTanti; Dery Ariswanto (G-Tech: Jurnal Teknologi Terapan, 2026)
Information and communication technology (ICT) is increasingly used to address urban environmental challenges, yet evidence on its specific roles in Smart Environment initiatives remains fragmented. This study systematically reviews the technologies, functional roles, and environmental outcomes of ICT-enabled Smart Environment development. A systematic literature search was conducted across six academic databases for studies published from 2020 to 2025. Of 1,879 initially identified records, 30 studies met the eligibility criteria and minimum quality threshold and were synthesized thematically. The findings identify the Internet of Things as the most frequently reported technology, complemented by artificial intelligence, cloud/fog/edge computing, digital twins, blockchain, smart grids, and other digital systems. ICT contributes through six interconnected functions: environmental sensing and monitoring, data integration, intelligent analytics, decision support, resource efficiency, and governance support. The main conceptual contribution is an integrative ICT-enabled Smart Environment framework linking ICT enablers, functional roles, application domains, and environmental outcomes. Although the reviewed studies generally report positive contributions, direct and comparable evidence of environmental improvement remains limited. Future research should evaluate integrated ICT architectures using measurable sustainability indicators.